A comparative analysis of urban development, economic level, and COVID-19 cases in Mexico City - R. Molina-Torres; O. Nolasco-Jauregui; E. E. Rodriguez-Torres; B. A. Itzá-Ortiz; L. A. Quezada-Tellez (Journal of Urban Management, 2021)
The pandemic caused by the SARS-CoV-2 virus spreads more rapidly in densely populated areas. The number of confirmed cases is counted by the millions in some countries, such as USA, Brazil, and Mexico. These three countries also report the world's highest cumulative death tolls caused by the disease as of February 2021. In this study, a comparative analysis of urban development, economic level, and the number of COVID-19 cases in Mexico City, is conducted. Mexico City, the capital city of Mexico, is among the most densely populated metropolitan areas and one of the largest financial centers in the continent. Among the sixteen municipalities, in which Mexico City is divided, there exist enormous economic and urban development gaps. Based in a comparability index (CI), this study found a correlation between the number of confirmed cases of the COVID-19 disease with the population density, the per capita income, and the dwelling occupancy index in each municipality.
Keywords: 710; COVID-19; per capita income; Mexico City; Dwelling occupancy; Population density